A Review on cold protective cloth by using fabric materials on various ambient temperature - Satish Kumar; Lakshmi Yadav (Innovative Research Thoughts, 2023)
Having to do one's duties or work under cold conditions is a worldwide issue. The design of cold-season protective gear is a complex process that must take into account the influence of many aspects, both external and internal, including weather conditions and the wearer's own physical, physicochemical, and mental characteristics. The purpose of this study is to offer a literature assessment on efforts to enhance cold-protecting cloth via the use of various textiles. Denser fabric is used for cold protection since it is more challenging to control ventilation and temperature in such a fabric. This study explores the various insulating materials now on the market and the fundamental aspects that go into the design of cold protective apparel.